2008
DOI: 10.1038/sj.bjc.6604780
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter species in cancers of the gallbladder and extrahepatic biliary tract

Abstract: Helicobacter species have been found in human bile and biliary tract (BT) tissue and are suspected to cause BT diseases, including gallbladder and extrahepatic cancers, collectively referred to in this work as BT cancers. We conducted a literature review of the epidemiological evidence linking the presence of Helicobacter species in bile or BT biopsies to BT cancers and benign diseases. Reports showed great variability with respect to study methods. Nine studies of BT cancers were identified, all with 30 or fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 43 publications
0
27
1
1
Order By: Relevance
“…Enterohepatic species of the genus Helicobacter (EHH) have become increasingly important as emerging pathogens (Collado et al, 2014;Fresia et al, 2017) due to their association with acute gastroenteritis, inflammatory bowel disease (Crohn's disease and ulcerative colitis) and liver, gallbladder and bile ducts diseases (Man et al, 2008;Martel et al, 2009;Bascuñana et al, 2011;Thomson et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterohepatic species of the genus Helicobacter (EHH) have become increasingly important as emerging pathogens (Collado et al, 2014;Fresia et al, 2017) due to their association with acute gastroenteritis, inflammatory bowel disease (Crohn's disease and ulcerative colitis) and liver, gallbladder and bile ducts diseases (Man et al, 2008;Martel et al, 2009;Bascuñana et al, 2011;Thomson et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Although EHH are frequently detected in clinical samples by PCR (Fox, 2002;Mateos-Muñoz et al, 2013;Fresia et al, 2017), only occasionally they are isolated using medium and atmospheric conditions designed for Campylobacter spp. According to the Bergey's Manual, there is no ideal method for the isolation of EHH and the recovery of these species is often optimized by the simultaneous use of selective and nonselective procedures .…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that few studies have addressed the presence of Helicobacter spp. in ECCA using a case-control study design, and those using PCR tests specific for H. hepaticus and H. bilis are even fewer [50]. Among these last studies, some reported a significantly higher frequency of Helicobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies of humans have evaluated the presence of Helicobacter species in biliary tracts of cancer patients versus controls. These studies have had significant differences in their methods of bacterial detection, including culture, DNA amplification, and immunohistochemistry (58,98). Controls have typically comprised subjects with biliary tract diseases such as gallstones or cholecystitis.…”
Section: Alterations Of Normal Host Responses Chronic Inflammationmentioning
confidence: 99%